Alfred Adler and the academic psychology - Lück, Helmut E. (2004)
This communication is concerned with the relation of individual psychology and academic psychology at the time of Alfred Adler, first a Freud`s follower and then a dissident. Adler`s ambivalent relation to academic psychology, caused by his failure in his habilitation attempt, and the anti-academic attitudes of some of his followers, are contrasted with the points of view of two academic psychologists: William Stern and Kurt Lewin.